Morphometric performances of Katingan cattle in Central Kalimantan - Bambang Ngadji Utomo; R.R Noor; C Sumantri; I Supriatna; E.D Gunardi (Indonesian Center for Animal Research and Development (ICARD), 2010)
The information of Katingan cattle as an indigenous cattle in Central Kalimantan is very limited, especially phenotypic characterization. A number of 72 heads, consist of 57 heads female and 15 heads male of Katingan cattle in adults category were used in this study. The samples were obtained from three sub districts in district of Katingan, those were Tewah Sanggalang Garing (Pendahara Village), Pulau Malan (Buntut Bali Village) and Katingan Tengah (Tumbang Lahang Village). The location were used as the variable of groups (subpopulation). This study was conducted to describe morphometric performance, which was analysed by discriminant and canonical to estimate the phylogenic relationship and to determine the discriminant variable among the group (subpopulation). The SAS package program version 6.0 and MEGA 2 program was used to analyze data. The observed parameters were body length, wither height, chest width, chest depth, chest circumference, hip heigth, hip width, head height, head length and head width. The chest depth and hip height of female cattle from group of Buntut Bali were lower (P < 0.05) than that of Pendahara and Tumbang Lahang groups. The parameter of: chest width, hip width and body length of Buntut Bali groups were higher (P < 0.05) than that of Pendahara and Tumbang Lahang groups. The average body weight of male Katingan cattle from Buntut Bali was higher (P < 0.05) than that of Pendahara and Tumbang Lahang groups but there were not different (P > 0.05) on bodyweight of female Katingan cattle among location. The highest similarity value was Katingan cattle from group of Tumbang Lahang (92,86%) followed by group of Pendahara (40.91%) and group of Buntut Bali (38.89%), repectivelly. Katingan cattle from group of Pendahara and Tumbang Lahang had closest genetic distance (1.406), while the longest genetic distance (2.046) was between group of Buntut Bali and group of Tumbang Lahang. Genetic distance between group of Buntut Bali and Pendahara was 1.929. Katingan cattle from Pendahara and Tumbang Lahang within one cluster. Body length in canonical structure 2 can be used as discriminant variable. Key Words: Katingan Cattle, Morphometric, Genetic Distance, Discriminant Analysis, Canonical